Where you'll find me: Risk, decisions, and the last climb of Kate Matrosova (Tantor Media, Inc., TMC Books LLC, 2017)
On Feb. 15, 2015, Kate Matrosova, an avid mountaineer, set off before sunrise for a traverse of the Northern Presidential Range in New Hampshire's White Mountains. Late the following day, rescuers carried her frozen body out of the mountains amid some of the worst weather ever recorded on these deceptively rugged slopes. At thirty-two, Matrosova was ultra-fit and healthy and had already summited much larger mountains on several continents. Her gear included a rescue beacon and a satellite phone. Yet, despite their best efforts, more than forty expert search and rescue personnel, a New Hampshire Army National Guard Blackhawk helicopter, and a Civil Air Patrol Cessna airplane could not reach her in time to save her. What went wrong? Where You'll Find Me offers possible answers to that question, demonstrating why Matrosova's story--what we know and what we will never know--represents such an intriguing and informative case study in risk analysis and decision-making.